Hadron collider probes of the quartic couplings of gluons to the photon and Z boson - John Ellis; Shao-Feng Ge; Kai Ma (Journal of High Energy Physics, 2022)
Abstract We explore the experimental sensitivities of measuring the gg → Zγ process at the LHC to the dimension-8 quartic couplings of gluon pairs to the Z boson and photon, in addition to comparing them with the analogous sensitivities in the gg → γγ process. These processes can both receive contributions from 4 different CP-conserving dimension-8 operators with distinct Lorentz structures that contain a pair of gluon field strengths, G ̂ μv a $$ {\hat{G}}_{μ v}^a $$ , and a pair of electroweak SU(2) gauge field strengths, W μv i $$ W_{μ v}^i $$ , as well as 4 similar operators containing a pair of G ̂ μv a $$ {\hat{G}}_{μ v}^a $$ and a pair of U(1) gauge field strengths, B μν . We calculate the scattering angular distributions for gg → Zγ and the Z → f ¯ f $$ \overline{f}f $$ decay angular distributions for these 4 Lorentz structures, as well as the Standard Model background. We analyze the sensitivity of ATLAS measurements of the Z(→ ℓ + ℓ − , ν ¯ ν $$ \overline{ν}ν $$ , q ¯ q $$ \overline{q}q $$ )γ final states with integrated luminosities up to 139 fb −1 at s $$ \sqrt{s} $$ = 13 TeV, showing that they exclude values ≲ 2 TeV for the dimension-8 operator scales, and compare the Zγ sensitivity with that of an ATLAS measurement of the γγ final state. We present combined Zγ and γγ constraints on the scales of dimension-8 SMEFT operators and γγ constraints on the nonlinearity scale of the Born-Infeld extension of the Standard Model. We also estimate the sensitivities to dimension-8 operators of experiments at possible future proton-proton colliders with centre-of-mass energies of 25, 50 and 100 TeV, and discuss possible measurements of the Z spin and angular correlations.